2021
DOI: 10.1111/jsr.13503
|View full text |Cite
|
Sign up to set email alerts
|

Does observance of Ramadan affect sleep in athletes and physically active individuals? A systematic review and meta‐analysis

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 92 publications
4
43
0
Order By: Relevance
“…Several reports showed disrupted circadian rhythms and reduced sleep quality during-lockdown in athletes ( 1 4 ), without taking into consideration the potential effect of Ramadan observance in addition to lockdown adherence. Indeed, Ramadan observance per se has been reported to reduce sleep quality and quantity in athletes and physically active individuals ( 11 , 16 ) whilst lockdown has also been reported to reduce sleep quality and increase insomnia severity in athletes ( 1 4 ). We have shown that, the proportion of Muslim athletes reporting poor (68%) and very poor (32%) sleep quality during-lockdown was higher than that observed in the overall sample of athletes (49 and 22%, respectively) ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several reports showed disrupted circadian rhythms and reduced sleep quality during-lockdown in athletes ( 1 4 ), without taking into consideration the potential effect of Ramadan observance in addition to lockdown adherence. Indeed, Ramadan observance per se has been reported to reduce sleep quality and quantity in athletes and physically active individuals ( 11 , 16 ) whilst lockdown has also been reported to reduce sleep quality and increase insomnia severity in athletes ( 1 4 ). We have shown that, the proportion of Muslim athletes reporting poor (68%) and very poor (32%) sleep quality during-lockdown was higher than that observed in the overall sample of athletes (49 and 22%, respectively) ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…As meal and physical activity timing are potent zeitgebers (from German synchronizers), Ramadan is a potent disrupter for Muslims' circadian rhythms in general and in particular Muslim athletes (8)(9)(10). Ramadan observance is accompanied by physiological (e.g., hypohydration, decreased body mass, and/or fat percent) (7) and behavioral (e.g., late meals, intentional nighttime wake ups, and reduced physical activities levels) (11,12) changes that affect Muslim athletes' training and sleeping behaviors. Indeed, recent systematic reviews reported that Ramadan observance could affect a wide range of physical performances even if many studies do not report any effect of Ramadan observance on certain physical activity performance measures (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed impairment of sleep quantity (i.e., nocturnal sleep duration) and quality and excessive daytime sleepiness (EDS) during Ramadan, possibly due to physiological and behavioral changes in diurnal and nocturnal activities. These activities include waking up for the predawn meal (Suhur) and dawn prayer, and practicing more activities at night such as social meetings, shopping, Quran reading groups, and prayers (e.g., Attarawih) (29)(30)(31).…”
Section: Introductionmentioning
confidence: 99%
“…The time lapse between sunset and dawn, and the resulting effects can drastically change according to the location’ latitude and time of the year ( Chamari et al, 2019 ). The obligation to eat only overnight span can lead to several changes in sleep scheduling ( Trabelsi et al, 2020a , 2021 ) and quality and meal timing and composition ( Trabelsi et al, 2020b , 2022 ) and previous studies have shown disturbances during the month of Ramadan in the quantity ( Leiper et al, 2008 ; Aziz et al, 2010 ; Herrera, 2012 ) and quality ( Zerguini et al, 2007 ; Chamari et al, 2016 ) of sleep, dietary intake ( Trabelsi et al, 2012a , b ; Abedelmalek et al, 2015 ), as well as water consumption ( Trabelsi et al, 2012a , b ; Aloui et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%